2018
DOI: 10.5530/pj.2018.3.89
|View full text |Cite
|
Sign up to set email alerts
|

Repairing Effects of Aqueous Extract of Kalanchoe pinnata (Lmk) Pers. on Lupus Nephritis Mice

Abstract: Kalanchoe pinnata (Lmk) Pers (KP) has an immunosuppressive effect on delayed-type hypersensitivity test. Based on it, this research aimed to determine the repairing effects of aqueous extract of KP on lupus nephritis mice and identified its active compound. The KP extract profile was determined using UPLC-QTOF-MS/MS instrument. We examined six mice groups consisting of three curative treatment groups, one standard group receiving prednisone, one preventive group receiving KP extract, and one healthy (healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…For the blood chemistry assay, the selected parameters were glucose, liver enzymes (ALT, AST), and renal function markers (urea, creatinine), as several studies have shown that B. pinnatum has antidiabetic/hypoglycemic activity [4,22,23]. Other studies have also reported hepatoprotective [12,24] and nephroprotective [25,26] effects.…”
Section: Discussionmentioning
confidence: 99%
“…For the blood chemistry assay, the selected parameters were glucose, liver enzymes (ALT, AST), and renal function markers (urea, creatinine), as several studies have shown that B. pinnatum has antidiabetic/hypoglycemic activity [4,22,23]. Other studies have also reported hepatoprotective [12,24] and nephroprotective [25,26] effects.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the extraction method, different processes can be observed in Table 10, ranging from the simple maceration [76,80,82,83,85] and simple blending [75,81] to more sophisticated and energy-consuming methods such as Soxhlet extraction [66,87], accelerated solvent extraction [71] or pressurized liquid extraction [74]. It is worth to notice that in the case of Kalanchoe leaves a solvent-free method based on pressing can be also employed [77,78]. The outcome of Table 10 is that for this biomass there are different methods available for the development of a clean and low energy-consuming process at a large scale.…”
Section: Recovery Methods and Performancementioning
confidence: 99%
“…Kalanchoe leaves are known in different parts of the world for their wide variety of beneficial properties in folk medicine. In fact, up to now they have shown to possess anti-inflammatory [66,[68][69][70][71][72][73][74], anti-leishmanial [69,[74][75][76][77] anti-hypersensitive activities [76,78,79], and to have refrigerant, depurative, disinfectant and hemostatic effect [66]. Furthermore, they have been successfully used in the treating of ulcers [70,71,80,81], rheumatism [71,80,81], infections [71,75,[81][82][83][84], fever [82,83,85], skin diseases [79,82,83,86], pulmonary infections [80],…”
Section: Kalanchoe Leavesmentioning
confidence: 99%
See 2 more Smart Citations